2015
DOI: 10.3807/josk.2015.19.1.007
|View full text |Cite
|
Sign up to set email alerts
|

Half mJ Supercontinuum Generation in a Telecommunication Multimode Fiber by a Q-switched Tm, Ho:YVO4Laser

Abstract: Up to ~520 µJ broadband mid-infrared (IR) supercontinuum (SC) generation in telecommunication multimode fiber (MMF) directly pumped by a 2.054 μm nanosecond Q-switched Tm,Ho:YVO4 laser is demonstrated. An average output power of 3.64 W is obtained in the band of ~1900 to ~2600 nm, and the corresponding optic-to-optic conversion efficiency is 67% by considering the coupling efficiency. The spectrum has extremely high flatness with negligible intensity variation (<2%) in the wavelength interval of ~2070 to ~2475… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The intricate nonlinear interactions emphasize the benefits of using a fiber shaper to control the spatiotemporal dimension of the nonlinear dynamics in order to achieve a targeted output in different dispersion regimes. Earlier studies have successfully demonstrated broadband supercontinuum generation using silica MMFs in longer pulse duration regimes 8 11 , 21 , 71 . In this work, we demonstrate a two-octave tunable source in the femtosecond regime, which enables applications in multiphoton microscopy due to its high-peak-power pulses.…”
Section: Resultsmentioning
confidence: 99%
“…The intricate nonlinear interactions emphasize the benefits of using a fiber shaper to control the spatiotemporal dimension of the nonlinear dynamics in order to achieve a targeted output in different dispersion regimes. Earlier studies have successfully demonstrated broadband supercontinuum generation using silica MMFs in longer pulse duration regimes 8 11 , 21 , 71 . In this work, we demonstrate a two-octave tunable source in the femtosecond regime, which enables applications in multiphoton microscopy due to its high-peak-power pulses.…”
Section: Resultsmentioning
confidence: 99%
“…Pulsed lasers of nearly 2 μm have played an important role in industrial, military, and scientific research fields. As an effective means to obtain a pulsed laser, passively Q-switched (PQS) technology has the advantages of simple structure, easy operation, and low cost. A high-quality saturable absorber (SA) is the key component for PQS.…”
Section: Introductionmentioning
confidence: 99%